Reaching Broader Audiences with Data Visualization - Lee, Bongshin; Choe, Eun Kyoung; Isenberg, Petra; Marriott, Kim; Stasko, John (IEEE Computer Graphics and Applications, 2020)
The visualization research community can and should reach broader audiences beyond data-savvy groups of people, because these audiences could also greatly benefit from visual access to data. In this paper, we discuss four research topics—personal data visualization, data visualization on mobile devices, inclusive data visualization, and multimodal interaction for data visualization—that, individually and collaboratively, would help us reach broader audiences with data visualization, making data more accessible.